Career choices in preventive and social medicine and other non-clinical specialties among medical students: Bangladesh perspective (South East Asia Journal of Public Health, 2013)
The main aims of the study were to identify the career choices in preventive and social medicine and non-clinical specialties along with the intended practice locations of medical students of Bangladesh. First, third and fifth year students of Bangladesh Medical College and Uttara Adhunik Medical College completed a self-reported questionnaire and were asked to choose three long-term choices from the given specialties. A small number of students opted for preventive and social medicine (3%), medical administration and management (3%), and basic medical science specialties. The popular choices among male and female were medical and surgical specialties (6%). More than 67% of respondents wanted to join private services and about 90% chose major cities as practice locations. As the majority of the students intended to specialize in established clinical specialties and subsequently practice in major cities, Bangladesh will suffer a chronic shortage of health personnel in those specialties and in rural areas. Major reforms are needed in medical education and healthcare to attract and retain a health workforce in those fields and to ensure equitable and high quality healthcare for those people who have little to no access to medical services. DOI: http://dx.doi.org/10.3329/seajph.v1i1.13224 South East Asia Journal of Public Health 2011:1:64-67